2015
DOI: 10.1149/2.0881507jes
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Electrodeposition Electrolyte Concentration on Microstructure, Optical Properties and Wettability of ZnO Nanorods

Abstract: ZnO nanorods were grown on ITO substrates with different concentration of electrolyte by electrodeposition method. Microstructure, surface topography, photoluminescence spectra, Raman spectra and water contact angle of the thin films were measured. The XRD results show all samples are hexagonal wurtzite and the intensity of diffraction peaks at (002) preferred orientation are strengthen as electrolyte concentration increase from 0.005 to 0.03 M. As the concentration increases, the average diameter, density and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Therefore, an oxygen-deficient surface will attract a water droplet, making the surface hydrophilic. 35,36 In our case, the PL analysis reveals that the intensity of the green emission of the nanorod (Fig. 4(c)) sample is at least one order of magnitude higher than that of the microrod sample (Fig.…”
Section: Study Of Temporal Wetting Propertymentioning
confidence: 49%
“…Therefore, an oxygen-deficient surface will attract a water droplet, making the surface hydrophilic. 35,36 In our case, the PL analysis reveals that the intensity of the green emission of the nanorod (Fig. 4(c)) sample is at least one order of magnitude higher than that of the microrod sample (Fig.…”
Section: Study Of Temporal Wetting Propertymentioning
confidence: 49%
“…Other authors [ 54 ] have also observed a decrease in the size of the matrix crystallites with an increase in the dispersed-phase concentration in the plating electrolyte.…”
Section: Resultsmentioning
confidence: 77%
“…The explanation for the decrease in the crystallite size of the cobalt matrix when increasing the dispersed-phase concentration in the plating electrolyte is as follows. The electrocrystallization or electrodeposition process is governed by two competitive steps: (i) nucleation site formation and (ii) crystal growth [ 54 ]. More nucleation sites will result in the reduced growth of the matrix crystallites.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations